Change in organizational culture and its importance in the organization - kither, djamila (Journal of Social Sciences and Humanities, 2020)
The subject of organizational culture is of utmost importance in the field of academic research in general and at the level of the departments of modern institutions, regardless of their size and the nature of their activities. The culture of the institution is a system, based in its structure on the values, beliefs and practices shared by its members, it is based on positive trends that support organizational effectiveness in order to improve organizational performance and push the institution towards its fixed objectives of adaptation to the broad and rapid changes of the external environment, to face the crises and to respond to the changes experienced by the institution. While the existence of the institutional culture's dimensions ¬ (individual initiative, risk tolerance, orientation, incentive for their employees to show frankly the conflicts and criticisms ...) contribute to achieve many benefits that make them unique to their culture and separate them from other organizations, and the culture of the institution has multiple functions and capabilities (building a culture of accountability, which gives members of the organization an organizational identity, decides between success or the failure of an offer, the development of a complete quality system ...) the degree of applicability and unity of these functions reflects the strength or weakness of the culture of the organization. On the other hand, the institution cannot guarantee its sustainability, stability and development without achieving a broad and global change in its organizational culture, by providing certain factors and relying on several conditions necessary to achieve the objectives of the change. In light of the above, it can be said that the change of culture of the institution requires a lot of time and the participation followed by one or many efforts added to that, the concentration on the appropriate and necessary conditions for the institution with the need to emphasize and pay great attention to the means that contribute to changing the culture of the institution, in order to meet the challenges posed by current developments, particularly in the global economic arena.